Perkembangan Keuangan Syariah dan Pertumbuhan Ekonomi di Indonesia: Analisis Hubungan Jangka Panjang dan Jangka Pendek: The Development of Islamic Finance and Economic Growth in Indonesia: An Analysis of Long-Term and Short-Term Relationships - Azwar Azwar; Arif Mashuri; Jamaluddin Majid (Program Studi Akuntansi Lembaga Keuangan Syariah, Politeknik Wahdah Islamiyah Makassar, 2025)
This study aims to analyze the short-run and long-run relationship between sukuk development and economic growth in Indonesia. The research employs a quantitative approach using annual time series data covering the period 2003–2022. The dependent variable is Gross Domestic Product (GDP) per capita (current US), while the independent variable is the value of Sukuk Outstanding (in billion rupiahs). The analysis utilizes the Autoregressive Distributed Lag (ARDL) model to examine both the long-term and short-term linkages between the two variables. The estimation results indicate that, in the long run, sukuk has a positive and significant effect on economic growth, confirming that an increase in sukuk issuance can strengthen national economic activity through the financing of productive, asset-based projects. In the short run, the Error Correction Model (ECM) results reveal an error correction coefficient of -0.084852, which is significant at the 1% level, implying an adjustment mechanism of approximately 8.48% per period toward long-run equilibrium. Although temporary negative effects are observed from previous sukuk issuances, the findings suggest that the market possesses a gradual self-correcting capacity. This study underscores the strategic role of sukuk in supporting sustainable economic growth in Indonesia, in line with Islamic finance principles that emphasize justice, stability, and social welfare.